All that glitters is not gold - "Antineutrophil cytoplasmic antibodies vasculitis presenting with acute respiratory distress syndrome mimic" - Ravi Sharma; Rajeev Kumar Bansal; Lalit Bharadia; Piyush Mathur (Wolters Kluwer Medknow Publications, 2020)
The systemic vasculitides are multifocal diseases characterized by the presence of blood vessel inflammation in multiple organ systems. Their clinical presentation is variable extending from self-limited illness to critical complications including diffuse alveolar hemorrhage and glomerulonephritis. Alveolar hemorrhage is a life-threatening manifestation of pulmonary vasculitis that can rapidly progress into acute respiratory failure requiring ventilatory support. We present the case of a 13-year-old patient admitted to the intensive care unit with respiratory distress and diffuse alveolar infiltrates in chest imaging that was later diagnosed as antineutrophil cytoplasmic antibodies-associated vasculitis. The report highlights the importance of differentiation between alveolar hemorrhage and acute respiratory distress syndrome of other etiology because alveolar hemorrhage is reversible with prompt initiation of treatment.